Dominance of Autochthonous Phytoplankton-Derived Particulate Organic Matter in a Low-Turbidity Temperate Estuarine Embayment, Gwangyang Bay, Korea - Riaz Bibi; Hee Yoon Kang; Dongyoung Kim; Jaebin Jang; Goutam Kumar Kundu; Goutam Kumar Kundu; Young Kyun Kim; Chang-Keun Kang (Frontiers in Marine Science, 2020)
In estuaries, the sources of organic matter, its composition, and its functional role in the coastal ecosystem food web are all influenced by dominant estuarine processes. We investigated seasonal variations in the quantity and composition of dissolved inorganic nutrients, suspended particulate matter (SPM), and phytoplankton across a low-turbidity estuarine–coastal continuum in Gwangyang Bay, South Korea. The narrow estuarine channel has a sharp salinity gradient (from 0 to around 30) and low SPM concentrations (<20 mg L–1). The channel carries river discharge, with a large quantity of nutrients (NO3 and SiO2), into the bay. The especially low SPM concentrations in the estuary (range: 2.0–29.1 mg L–1), and generous nutrient source, create an exceptionally low-turbidity condition in the water column and high primary productivity with no conspicuous spatial or seasonal trends. Gradually increasing δ13C values, low POC:Chla (<200), and low molar C:N (4–8) in the SPM, together with higher Chla concentrations at low SPM locations along the longitudinal transect, suggest that local production of phytoplankton has a strong influence on the distributional patterns of particulate organic matter. Short water-residence times, within the bay system, impede the accumulation of diverse-origin organic matter. The community composition of phytoplankton, distinguished by their size group, also plays a role in characterizing SPM quantity and composition. The results indicate that autochthonous pelagic production governs biogeochemical features in the low-turbidity estuarine embayment, contrasting with a prevalence of allochthonous organic matter, and its active processing, in highly turbid and/or longer residence-time systems.